Code generation for hardware accelerated AES - MANLEY, RAYMOND KEITH SCOTT; GREGG, DAVID (IEEE, 2010)
Data must be encrypted if it is to remain confidential when sent over computer networks. Encryption solves many problems involving invasion of privacy, identity theft, fraud, and data theft. However for encryption to be widely used, it must be fast. The problem is so important that new Intel processors provide hardware support for encryption. These instructions implement key stages of the Advanced Encryption Standard (AES), allowing encryption to be completed more quickly and using less power. The AES algorithm consists of several 'rounds' of encryption, each of which involves a relatively complicated computation. This new hardware support allows an entire round to be implemented with just a single instruction. An implementation of the AES algorithm using these instructions contains several code sections that can be fine tuned for optimal performance. However, these optimizations are usually done by hand, which can be a lengthy, labour intensive process. We present a system that can generate billions of variants of the AES encryption code to find the best solution for a particular microarchitecture. We apply both common loop optimizations and ones specific to AES. We evaluate the generated code on hardware with built-in AES support using both selective-brute force and guided searches. Our generator achieves significant speedups over a straightforward implementation of the code.
21st IEEE International Conference on Application-specific Systems Architectures and Processors
PUBLISHED
Rennes, France
Keywords: Computer Science; encryption; Smart & Sustainable Planet